STREATEGI PEMBELAJARAAN INOVATIF UNTUK MENINGKATKAN LITERASI DAN NUMERASI PADA MADRASAH IBTIDAIYAH - Afriantoni Afriantoni; Rima Tahira; Reza Shakila Azzahra; Aisya Fitri (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The improvement of literacy and numeracy quality is a major challenge in primary education in Indonesia, including in madrasah ibtidaiyah. Various international reports such as the Programme for International Student Assessment (PISA) and the National Assessment (AN) show the low achievement of Indonesian students in reading, mathematics, and science. This condition is worsened by the dense madrasah curriculum, limited facilities and infrastructure, and the dominance of traditional teacher-centered learning methods. This study aims to analyze innovative learning strategies relevant to improving literacy and numeracy skills among madrasah ibtidaiyah students while maintaining Islamic identity. The method used is library research with a descriptive-analytical approach through a review of academic literature, educational policies, and student achievement data. The study results indicate that strategies such as Project-Based Learning, digital technology integration, and context-based approaches linked to everyday life and religious values are effective in developing students' critical, creative, collaborative, and communicative thinking skills. The implementation of these strategies not only increases learning motivation but also makes literacy and numeracy more applicable and meaningful as life skills aligned with the teachings of the Qur'an and Hadith. Thus, innovative learning strategies have the potential to become an important instrument in improving the quality of Islamic primary education in Indonesia while shaping a generation that is intelligent, critical, creative, and of noble character.